Congenital Parameatal Urethral Cyst in The Male: A Case Report and Review of Literature - Oktaviani, Dian Paramita; Hoetama, Sakti; Soetojo, Soetojo (Folia Medica Indonesiana, 2020)
Purpose:: To report one case of parameatal urethral cyst. Background : Parameatal urethral cyst is a scarce congenital condition that was first reported in two males in 1956, until now in reported literature only found less than 50 cases, in both adults and children. Our patient, case of parameatal urethral cyst in a 5 years old boy is reported. Complete excision with total removal of the epithelium of the cyst is required management for the treatment and prevention of cyst reocurrance. Case Report:a 5 years old male with a cystic lesion around urethral meatus since birth. At least 5 month the parents complain distorted urinary flow and poor appearance, and no other urinary symptom, no history of trauma. On physical examination, cystic mass with spherical shape which was about 0.5 cm in diameter was found around external meatus. There was no inflammatory sign. And there was normal blood laboratory (blood counts and blood chemistry) and urine laboratory (urine analysis and urine culture). The patient undergo completely excision of the cyst under general anaesthesia, and remove all of the lining epithelium. Good appearance results were obtained after 2 months follow up, without meatal strictures and urine stream problems, and no postoperative complications or recurrence. Pathological : Squamous epithelial, granulation tissue with chronic inflamation. Conclusions :Parameatal urethral cyst is a very rare benign condition that is asymptomatic in most of the cases. It may be present since birth or appear later and is prevalent in young males. Its etiology remains unclear and treatment is by complete surgical excision to avoid complications and recurrence. Good cosmetic results were obtained in this case without any recurrence at two months follow up.Parameatal cyst, Glans penis, external meatus urethra, Urethral cyst